Synthesis, characterization, molecular docking studies of new alkyl derivatives of 5-(2-bromo-4-fluorophenyl)-4-ethyl-4H--1, 2, 4-triazole-3-thiol - Shcherbyna, R. O.; Kalchenko, V. V.; Kulish, S. M.; Salionov, V. O.; Morozova, L.; Nedorezaniuk, N.; Mazur, O.; Щербина, Роман Олександрович; Кальченко, Валерій Володимирович; Куліш, Сергій Миколайович; Саліонов, Володимир Олександрович (My University, 2023)
The main goal of this article is to present the results of the synthesis of new alkyl derivatives of 5-(2-bromo- 4-fluorophenyl)-4-ethyl-4H-1,2,4-triazole-3-thiol and molecular docking studies against COX-1 and COX- 2. Previous studies have established a wide range of biological activity of 1,2,4-triazole derivatives. Therefore, it was essential to determine how a new series of 1,2,4-triazole derivatives would provide potential anti-inflammatory activity. To reach the goal, raw alkyl derivatives of 5-(2-bromo-4-fluorophenyl)- 4-ethyl-4H-1,2,4-triazole-3-thiols (2a-2i) from 5-(2-bromo-4-fluorophenyl)-4-ethyl-4H-1,2,4-triazole- 3-thiol (1e) were obtained. The structure of the synthesized compounds was confirmed by 1H-NMR elemental analyses. The individuality and purity of compounds were confirmed by the method of liquid chromatography-mass spectrometry. These compounds have a relatively simple synthesis scheme, which gives them an advantage in creating a potential drug, and the appearance of alkyl radicals in the molecule should positively affect pharmacokinetic indicators, stability, selectivity, and bioavailability. An in silico study was conducted for the synthesized compounds, namely molecular docking, in relation to the interaction with COX-1 and COX-2. Based on the selectivity indexes of binding modes observed for the selected compounds (2e, 2g) with active COX-1 centers, it was found that compounds can reliably exhibit their anti-inflammatory effect through the prostaglandin biosynthesis pathway, inhibiting COX-1 instead of COX-2. The effect of hydrophobic interactions of alkyl groups of 1,2,4-triazole derivatives on changes in affinity and selectivity to COX-1 or COX-2 has also been proven. Therefore, derivatives of 1,2,4 are promising candidates for improvement, further study, and future development of new, more powerful antiinflammatory drugs for therapeutic use.
Keywords: 1,2,4-triazole; synthesis; molecular docking; anti-inflammatory activity; in silico